A systematic review and meta-analysis of the effects of Qigong and Tai Chi for depressive symptoms. Issue 4 (August 2015) - Liu, Xin; Clark, Justin; Siskind, Dan; Williams, Gail M.; Byrne, Gerard; Yang, Jiao L.; Doi, Suhail A.
Highlights Qigong has been shown to be beneficial for reducing depressive symptom severity. Tai Chi appears to be ineffective in reducing depressive symptom severity. All other forms of care do not result in a change in depressive symptom severity.